2021
DOI: 10.3390/s21051754
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PTFE Coating on PDMS Surfaces for Inhibition of Hydrophobic Molecule Absorption for Increased Optical Detection Sensitivity

Abstract: Polydimethylsiloxane (PDMS) is a polymer widely used for fabrication and prototyping of microfluidic chips. The porous matrix structure of PDMS allows small hydrophobic molecules including some fluorescent dyes to be readily absorbed to PDMS and results in high fluorescent background signals, thereby significantly decreasing the optical detection sensitivity. This makes it challenging to accurately detect the fluorescent signals from samples using PDMS devices. Here, we have utilized polytetrafluoroethylene (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…However, most embryo culture media contain bovine serum albumin (BSA), which serves as a surface coating for substrates and helps avoid embryo retention on polystyrene or glass substrates. Although ostensibly BSA pretreatment would mitigate any absorption of small molecules by PDMS substrates, observations from Kim et al suggest that BSA is not effective in blocking absorption in PDMS substrates for an extended time [23,27]. Similar findings were reported with a cotreatment of fibrinogen and BSA on a PDMS surface, where fibrinogen adsorption was impeded for about 6 h in favour of diffusion-limited BSA adsorption but was later allowed to coat the surface [28].…”
Section: Introductionmentioning
confidence: 68%
“…However, most embryo culture media contain bovine serum albumin (BSA), which serves as a surface coating for substrates and helps avoid embryo retention on polystyrene or glass substrates. Although ostensibly BSA pretreatment would mitigate any absorption of small molecules by PDMS substrates, observations from Kim et al suggest that BSA is not effective in blocking absorption in PDMS substrates for an extended time [23,27]. Similar findings were reported with a cotreatment of fibrinogen and BSA on a PDMS surface, where fibrinogen adsorption was impeded for about 6 h in favour of diffusion-limited BSA adsorption but was later allowed to coat the surface [28].…”
Section: Introductionmentioning
confidence: 68%
“…Hence, these molecules are easily absorbed by the PDMS, which ultimately interferes with light tracking. Of interest is that recently, covering the PDMS with polytetrafluoroethylene (PTFE) has been proposed as a practical solution, which can have a significant contribution to increasing the sensitivity of optical detecting ( 134 ). Another drawback of OOC systems is the formation of bubbles in microfluidic channels, which is considered as a barrier to creating a suitable chip in modeling diseases ( 135 ).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Polytetrafluoroethylene (PTFE) can be used for microfluidic devices due to its thermo-processability, chemical inertness, and [52]. In 2021, Yao et al [53] showed that PTFE could be used to inhibit the absorption of small hydrophobic molecules in PDMS. Another problem is that the reproducibility of OOC manufacturing varies depending on the properties of materials used, hydrophilic and hydrophobic surface treatment, the ECM used, and the storage conditions of the manufactured chip.…”
Section: Figmentioning
confidence: 99%